Transfer task (pre- and post-test) design and information alignment. - Denise Moerel (9080849) (2025)
(A) The same 1-back task was used in a pre- and post-test. In this task, participants saw a stream of images, presented at 2 Hz. The task of the participants was to count the number of 1-back targets (i.e. same image presented twice in a row) for each stream. The agreed-upon categories from the main task were not relevant for the pre- and post-test. (B) The alignment of representations between the two participants in the real pairs for the pre-test (orange) and post-test (green). The shaded areas around the plot lines show the 95% confidence interval, and cluster-corrected p values <.05 are given below the plot in the same colors. (C) The difference in information alignment between real pairs and pseudo-pairs, not constrained by the same rules (real—pseudo-pairs). This difference shows the part of the alignment that is not driven by visual information. All plotting conventions are the same as for Fig 6B.